Avian community responses to post‐fire forest structure: implications for fire management in mixed conifer forests. (28th September 2015) - White, A. M.; Manley, P. N.; Tarbill, G. L.; Richardson, T. W.; Russell, R. E.; Safford, H. D.; Dobrowski, S. Z.
Abstract: Fire is a natural process and the dominant disturbance shaping plant and animal communities in many coniferous forests of the western US. Given that fire size and severity are predicted to increase in the future, it has become increasingly important to understand how wildlife responds to fire and post‐fire management. The Angora Fire burned 1243 hectares of mixed conifer forest in South Lake Tahoe, California. We conducted avian point counts for the first 3 years following the fire in burned and unburned areas to investigate which habitat characteristics are most important for re‐establishing or maintaining the native avian community in post‐fire landscapes. We used a multi‐species occurrence model to estimate how avian species are influenced by the density of live and dead trees and shrub cover. While accounting for variations in the detectability of species, our approach estimated the occurrence probabilities of all species detected including those that were rare or observed infrequently. Although all species encountered in this study were detected in burned areas, species‐specific modeling results predicted that some species were strongly associated with specific post‐fire conditions, such as a high density of dead trees, open‐canopy conditions or high levels of shrub cover that occur at particular burn severities or at a particular time following fire. These results indicate that prescribed fire or managed wildfire which burns at low to moderate severity without at least some high‐severity effects is both unlikely to result in the species assemblages that are unique to post‐fire areas or to provide habitat for burn specialists. Additionally, the probability of occurrence for many species was associated with high levels of standing dead trees indicating that intensive post‐fire harvest of these structures could negatively impact habitat of a considerable proportion of the avian community.